Adsorption efficiency and isotherms of COD and color using limestone and zeolite adsorbents - Rosli, Mohd Arif; Daud, Zawawi; Awang, Halizah; Ab Aziz, Nur Adila; Ridzuan, Mohd Baharudin; Abubakar, Mahmoud Hijab; Adnan, Mohd Shalahuddin; Tajarudin, Husnul Azan (Penerbit UTHM, 2018)
Leachate is a liquid generated due to rainwater percolation through the wastes in a landfill or dumping site that may contain high levels of organic matter including both biodegradable and non-biodegradable which major source of water pollution. In this research work, landfill leachate has been characterized and found to contain very high COD and color. Adsorption process was performed to find out the performance of different combinations ratio between limestone (LS) and zeolite (ZEO). The removal efficiencies of different ratios were examined for reduction of COD and color. The optimum mixture ratio of adsorbents (LS:ZEO) at 10:30 and 15:25 were found to be more effective in reducing COD and color respectively as compared with the use of individual media. The highest removal percentage were found at approximately 55% of COD and 76% of color with 120 minutes of contact time, 200 rpm in shaking speed at pH7. The Langmuir adsorption isotherm model exhibited a better fit with high correlation R2 =0.9991 for COD and R2 =0.9827 for (color) respectively, which implies that the adsorption of leachate in this study onto LS-ZEO is homogeneous with monolayer. It was observed that limestone and zeolite mixture provides an alternative medium for removing COD and color at a considerably lower cost.